New technologies and developing countries: Prospects and potential - Katherin Marton; Rana K. Singh (Intereconomics, 1992)
Technological innovations in informatics and other new technologies are having a major impact on most production and service sectors in industrialized countries. Inadequate transfer of such technologies to developing countries, with a few notable exceptions, is increasing the technology gap and reducing competitive capability in these countries. Far-reaching policy changes and a new emphasis on technological development must be made by developing economies in order to avail themselves of the growing potential of new and emerging technologies.
Keywords: 330; Technology